PENGARUH ETNOMATEMATIKA DAKON TERHADAP NUMERASI DAN KEMAMPUAN MOTORIK HALUS PADA ANAK USIA 5-6 TAHUN - Nuri Arifiah Romadhoni; Ruqoyyah Fitri; Sri Setyowati (Universitas Islam Negeri (UIN) Sumatera Utara, 2024)
This study aims to prove the results of media utilization for classroom learning in children aged 5-6 years. Traditional dakon games, as part of ethnomathematics, have great potential to develop children's cognitive abilities, including numeracy and fine motor skills. This study aims to deeply reveal the influence of dakon games on the development of both aspects in early childhood. The research method used is a Quasi experiment involving a number of children as research subjects. During the research period, children routinely played dakon while observing the development of their numeracy and fine motor skills. Data were collected through observation (Pretest and Posttest) and documentation of playing activities. The results of the study showed that dakon games have a significant influence in improving children's numeracy and fine motor skills. Children learn the concept of numbers, addition, subtraction, and patterns through dkon games. In addition, the activity of picking up and moving dakon seeds also helps improve hand-eye coordination and other fine motor skills. These findings indicate that dakon games can be an effective learning medium for developing numeracy and fine motor skills in early childhood. The use of traditional games in the context of mathematics learning not only makes learning more fun, but also enriches children's understanding of mathematical concepts in their cultural context